Determining The Independence and Professional Skills on Audit Quality at the The General Election Supervisory Agency (BAWASLU) of Indonesia - Lubis, Asmin Safari; Mulya, Hadri (International Journal of Social Science and Business, 2021)
Â This study aims to determine the effect of Auditor Competence, Auditor Independence and Professional Skills on Audit Quality at the General Election Supervisory Agency of the Republic of Indonesia (Bawaslu RI) and Provinces throughout Indonesia. The research model describes a conceptual framework as a guide as well as a flow of thought in developing hypotheses. The model in this study describes the influence of personal auditor factors consisting of competence, independence, professional skills on audit quality. The data collection technique in this study used multiple regression analysis using the Eviews program. Data analysis techniques include descriptive statistical tests, research instrument tests, classical assumption tests, model determination tests, and hypothesis testing. The results of the study indicate that competence has a positive effect on audit quality at the RI Bawaslu. These results can be used as consideration by the RI Bawaslu to be able to further improve the quality of audits on auditors, because the higher the competence of the auditors, the higher the audit quality. Independence does not have a positive effect on audit quality at the RI Bawaslu. Professional skills have a positive effect on audit quality at the RI Bawaslu. Professional skills are important things that must be applied by every public accountant in carrying out their professional work in order to achieve adequate audit quality.